Observational study of hemodynamic events during interfacility transit of critically ill patients in a 5G tele-ambulance connected to Tele-ICU - Dharanindra Moturu; Ramesh Babu Potineni; Supriya Rayana; Mohammad Noor Shaik; Naga Suvarna Maddu; Kavya Sruthi Grandhi (Egyptian Journal of Critical Care Medicine)
Abstract Aims and background Inter-hospital transportation of critically ill patients has been a challenge and a high-risk process in middle- and low-income countries across the world due to many causes, like poor road infrastructure. This study aims to evaluate the hemodynamic events during inter-hospital transfer using an indigenous remote monitoring system built into a tele-ambulance. Materials and methods A prospective, multicenter, observational study of hemodynamic events in critically ill patients transferred from the periphery to tertiary care hospitals in a 5G technology-based tele-ambulance connected to a centralized Tele-Intensive Care Unit. Results A total of 612 patient transfers were studied. The most frequent diagnosis among transferred patients was heart failure with reduced ejection fraction (15.5%), followed by septic shock (11.1%) and acute ischemic stroke (10.1%). During the transfers, 97 hemodynamic events were detected. The most frequent events were hypotension (5.2%), tachycardia (4.2%), hypoxia (2.4%), and bradycardia (1.9%). Ventricular tachycardia (1.14%) and non-sustained ventricular tachycardia (0.4%) were also documented. Intensivists at the Tele-Intensive Care Unit hub identified and provided real-time instructions to the medical staff accompanying the patient, ensuring immediate management and stabilization of the patients. Conclusion A 5G-enabled smart ambulance system integrated with a Tele-Intensive Care Unit hub could effectively support the remote monitoring and management of critically ill patients during inter-hospital transfers. This indigenous system uses the existing 5G network, hardware, and software technology with an intensivist monitoring the patients in transit. This study provided proof of the principle that hemodynamic events can be detected and acted upon in critically ill patients in transit.